Transduodenal ampullectomy for ampullary tumor - Yun Kyung Jung; Seung Sam Paik; Dongho Choi; Kyeong Geun Lee (Asian Journal of Surgery, 2021)
Summary: Background: Transduodenal ampullectiomy (TDA) is a surgical local excision method that can be performed in patients with ampullary tumors, but it has not been widely used clinically. Recently, TDA is considered as a good alternative surgical technique in patients who are unable to perform the endoscopic ampullectomy (EA) or pancreaticoduodenectomy (PD) for various reasons. The purpose of this study is to evaluate the surgical outcomes of TDA and the clinicopathological significance of pathologic findings in TDA. Methods: We reviewed the medical records of 31 patients diagnosed as ampullary tumor and underwent TDA from March 2004 to December 2019 in a single center. Results: All 31 patients were planned to perform TDA, and 4 of them were converted to PPPD due to the marginal status results of frozen biopsy. Of the 31 patients, 19 were diagnosed with malignancy and 12 were diagnosed with benign. Of the 18 patients who were diagnosed as malignancy in final biopsy, only 9 patients (50%) were diagnosed with malignancy on the preoperative endoscopic biopsy. In 15 patients who underwent only TDA for malignancy, there was no recurrence during the follow-up period (mean: 51.1 months, range: 19–137). Conclusions: In benign ampullary tumor, TDA is a choice of treatment for patients who are unsuitable for endoscopic ampullectomy. TDA may be considered as an alternative operation in highly selective patients with early ampullary cancer (Tis and T1). Further studies on consensus of TDA indication for ampullary tumor will be needed in the future.